2015
DOI: 10.1017/s0031182015000086
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of malaria infections in western lowland gorillas inhabiting Dzanga Sangha Protected Areas, Central African Republic

Abstract: African great apes are susceptible to infections with several species of Plasmodium, including the predecessor of Plasmodium falciparum. Little is known about the ecology of these pathogens in gorillas. A total of 131 gorilla fecal samples were collected from Dzanga-Sangha Protected Areas to study the diversity and prevalence of Plasmodium species. The effects of sex and age as factors influencing levels of infection with Plasmodium in habituated gorilla groups were assessed. Ninety-five human blood samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 54 publications
2
31
1
1
Order By: Relevance
“…Faecal detection rates of Plasmodium infection were found to be higher in younger individuals of P. t. verus (De Nys et al, 2013) and G. g. gorilla (Mapua et al, 2015) as well as in pregnant females of P. t. verus (De Nys et al, 2014). This probably reflects changes in the frequency of new infections and/or in parasite densities induced by variation in susceptibility to these parasites due to age and pregnancy status.…”
Section: Extrinsic and Intrinsic Determinants Of Plasmodium Infectionmentioning
confidence: 93%
See 1 more Smart Citation
“…Faecal detection rates of Plasmodium infection were found to be higher in younger individuals of P. t. verus (De Nys et al, 2013) and G. g. gorilla (Mapua et al, 2015) as well as in pregnant females of P. t. verus (De Nys et al, 2014). This probably reflects changes in the frequency of new infections and/or in parasite densities induced by variation in susceptibility to these parasites due to age and pregnancy status.…”
Section: Extrinsic and Intrinsic Determinants Of Plasmodium Infectionmentioning
confidence: 93%
“…P. praefalciparum, P. adleri and P. blacklocki (Liu et al, 2010(Liu et al, , 2016Prugnolle et al, 2010), and two non-Laverania species, i.e. P. vivax- (Liu et al, 2014) and ovale-like parasites (Mapua et al, 2015) (Fig. 1b).…”
Section: Parasite Diversity Distribution and Prevalence In African Gmentioning
confidence: 99%
“…Finally, most primate species (e.g., the ape Laverania [5]) appear to be either incapable of crossing species boundaries or do so inefficiently. Although P. malariae and P. ovale parasites have also been isolated from African great apes [5,78,79], the directionality of transmission (i.e., ape-to-human or human-to-ape) currently remains unclear.…”
Section: Figurementioning
confidence: 99%
“…Since 2007 we have been systematically surveying parasite infections of humans, western lowland gorillas and other wildlife inhabiting Dzanga Sangha Protected Areas (DSPA), Central African Republic (CAR), as part of an ongoing health-monitoring programme [5, 9]. Previous research has shown that both gorillas in DSPA and chimpanzees in Kalinzu Forest Reserve (KFR), Uganda were infected with strongylid nematodes [9], (Hasegawa and Pafčo, unpublished data) and with malaria parasites Plasmodium spp.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, studies in NHPs focused on the genetic diversity of Plasmodium spp. [3] and/or ecological aspects [5], no study has investigated co-infections with malaria and other pathogens.…”
Section: Introductionmentioning
confidence: 99%